Archaea in the Mycorrhizosphere of Boreal Forest Trees - Bomberg, Malin (Helsingin yliopisto, 2010)
Archaea were long thought to be a group of ancient bacteria, which mainly lived in extreme environments. Due to the development of DNA sequencing methods and molecular phylogenetic analyses, it was shown that the living organisms are in fact divided into three domains; the Archaea, Bacteria and the Eucarya. Since the beginning of the previous decade, it was shown that archaea generally inhabit moderate environments and that these non-extremophilic archaea are more ubiquitous than the extremophiles. Group 1 of non-extreme archaea affiliate with the phylum Crenarchaeota. The most commonly found soil archaea belong to the subgroup 1.1b. However, the Crenarchaeota found in the Fennoscandian boreal forest soil belong to the subgroup 1.1c. The organic top layer of the boreal forest soil, the humus, is dominated by ectomycorrhizal fungal hyphae. These colonise virtually all tree fine root tips in the humus layer and have been shown to harbour distinct bacterial populations different from those in the humus. The archaea have also been shown to colonise both boreal forest humus and the rhizospheres of plants. In this work, studies on the archaeal communities in the ectomycorrhizospheres of boreal forest trees were conducted in microcosms. Archaea belonging to the group 1.1c Crenarchaeota and Euryarchaeota of the genera Halobacterium and Methanolobus were detected. The archaea generally colonised fungal habitats, such as ectomycorrhizas and external mycelia, rather than the non-mycorrhizal fine roots of trees. The species of ectomycorrhizal fungus had a great impact on the archaeal community composition. A stable euryarchaeotal community was detected especially in the mycorrhizas, of most of the tested Scots pine colonising ectomycorrhizal fungi. The Crenarchaeota appeared more sporadically in these habitats, but had a greater diversity than the Euryarchaeota. P. involutus mycorrhizas had a higher diversity of 1.1c Crenarchaeota than the other ectomycorrhizal fungi. The detection level of archaea in the roots of boreal ...